ÃCIDO GIBERÉLICO: ALGUMAS OBSERVAÇÃ•ES SÃ”BRE UMA APLICAÇÃO EM CAPIM COLONIÃO - Freitas, Luis M. Martins de; McLung, A. C.; Quinn, L. R. (REVISTA DE AGRICULTURA, 2015)
ÃCIDO GIBERÉLICO: ALGUMAS OBSERVAÇÃ•ES SÃ”BRE UMA APLICAÇÃO EM CAPIM COLONIÃO